Uma análise comparativa: estratégias utilizadas pelos professores no ensino de Libras em uma instituição em Caraúbas-RN - Dantas, Uberlânia Souza do Vale (Universidade Federal Rural do Semi-Árido, 2019)
The present research deals with the need for strategies that facilitate the practice and teaching of the Brazilian Sign Language (LIBRAS). In this way, recognition is very important, as well as a more detailed look at this theme. It can be seen that the difficulties and challenges are constant in the classroom, especially when there is a lack of methodological teaching strategies. In this sense, it is necessary to make a comparative analysis and reflections regarding the teaching practices. Considering a proposal of the strategies of the teaching of Libras used by teachers in the beginnings classes of the course of Libras of an institution in Caraúbas/RN, and analyzing the context of the classroom, we had to describe which strategies are used in the school by teachers in the process of teaching the Sign Language. Therefore, we believe that the impact of this research will contribute to the teaching process for future professionals in this area, and will allow the expansion of several strategies to be used in the teaching and learning of Libras. We focus on the theories of the discussions about perceptions in the teaching of Libras (FELIPE, 2001, PERLI, 2002, LODI and CAPORALI, 2004) and strategy of didactic material (LEITE, 2001b, 2004, GESSER 2006, 2009, WILCOX and WILCOX 2005). The methodology, in an exploratory way, consisted of the observation and recording of two (2) meetings in Libras classes in a classroom, as well as an analysis of teaching material in the teaching of Libras for deaf and listener teacher. Among the methodological tools, we applied questionnaires to the teachers, who also served as corpus. Thus, we present as methodologies some visual strategies through the analysis of the discussions about the teachers that use the methodology applied in the classroom, and the results of the experiential school context. Finally, we consider that the positive and negative results of this research contributed to other future research since there is still too much to investigate when we talk about this topic.
Keywords: Análise comparativa; Estratégias; Ensino de Libras; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS